The Role of Promotional Media in Developing Sustainable Mining Heritage Tourism - Muhardi; Oktini, Dede; Fadhilah, Arief; Aufa, Muhammad (Mediator: Jurnal Komunikasi, 2023)
Open Pit Nam Salu tourist area, a Belitung National Geopark that has received recognition as a UNESCO Global Geopark, is one of the mining heritage-based tourist attractions visited by tourists from several countries from all continents of the world. For this reason, this research aims to analyze the role of promotion media in developing sustainable tourism on mining heritage. The method used in this research is descriptive qualitative using the Systematic Literature Review method, supported by interview and documentation methods. The study was conducted in Belitung, Bangka Belitung Province, Indonesia. The results show that promotional media is essential in helping the development of sustainable mining heritage tourism. The dominant promotional activities the Open Pit Nam Salu tourist attraction management carries out are advertising and digital/internet marketing. Then, regarding the sustainability of mining heritage tourism, at least three pillars must be met, starting from the environmental, social, and economic pillars.